Feed-forward control of a vehicle with single-wheel actuators - Moseberg, Jan-Erik; Roppenecker, Günter (19th IFAC World Congress on International Federation of Automatic Control, IFAC 2014, 2014)
For the horizontal motion of a vehicle with single-wheel actuators a model-based feed-forward control is derived. Using the accelerator and brake pedal position as well as the steering wheel angle, the feed-forward control generates a desired vehicle motion together with appropriate longitudinal and lateral forces on the vehicle mass and a corresponding yaw moment. Since no detailed vehicle model, e.g., the single-track model, is required it is possible to tune the horizontal vehicle dynamics arbitrarily without changing the vehicle's geometry. Subsequently, the obtained forces and the yaw moment are allocated to the eight horizontal tire forces. Since the vehicle considered is over-actuated a secondary objective, i.e., the safety maximization, can be pursued in addition to realizing the desired vehicle motion. Solving this optimization problem numerically in a real vehicle is time-critical, so an analytical solution is introduced.
Keywords: Control architectures in automotive control; Nonlinear and optimal automotive control; Vehicle dynamic systems